2015
DOI: 10.1177/0972150915569928
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Risk Factors Influence on Intention to Continue Using Internet Banking among Malaysians

Abstract: The objective of the present study is to identify which are the risk factors that influence the intention to continue using Internet banking in Malaysia. The primary participants are personal Internet banking users in Peninsular Malaysia. Data was collected through a self-administered questionnaire which employed the drop-off and pick-up (DOPU) technique. The questionnaires were distributed through this method to the respective bank branch managers who were willing to distribute to their customers. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 55 publications
3
35
1
Order By: Relevance
“…Kassim and Ramayah (2015) define BI as a measure of one’s willingness to exert effort while performing certain behaviours. The extent of effectiveness of the system depends on how the users feel for the system; if the users do not rely upon the system and its information, their behaviour towards the system could be negative (Pikkarainen et al, 2004).…”
Section: User Attitude and Intention To Adopt Mobile Bankingmentioning
confidence: 99%
See 1 more Smart Citation
“…Kassim and Ramayah (2015) define BI as a measure of one’s willingness to exert effort while performing certain behaviours. The extent of effectiveness of the system depends on how the users feel for the system; if the users do not rely upon the system and its information, their behaviour towards the system could be negative (Pikkarainen et al, 2004).…”
Section: User Attitude and Intention To Adopt Mobile Bankingmentioning
confidence: 99%
“…Therefore, it is seen that the intention to adopt mobile banking would be influenced by not only the technology adoption factors but also by the attitude towards mobile banking. Kassim and Ramayah (2015) in their study on Internet banking usage in Malaysia found attitude to be a significant factor influencing the intention to continue using Internet banking. This confirms findings from earlier studies (Akturan & Tezcan, 2012; Al-Somali et al, 2009; Heijden et al, 2003; Khasawneh, 2015; Montazemi & Saremi, 2015; Nasri & Charfeddine, 2012; Suh & Han, 2003) that have shown a direct influence of technology adoption factors and user attitude on BI.…”
Section: Implications For Academiamentioning
confidence: 99%
“…Thus, perceived enjoyment has an effect on both attitude and consumers' behavioural intention towards using a particular website. Kassim and Ramayah (2015) reported that social risk, time-loss risk, opportunity cost risk and perceived usefulness are significant factors influencing the attitude of online shoppers.…”
Section: Relationship Between Web Experience and Perceived Enjoymentmentioning
confidence: 99%
“…Venkatesh and Davis (2000) extended the original TAM model to explain the perceived usefulness and usage intentions in terms of the social influence and cognitive instrumental processes. Kassim and Ramayah (2015) have used this method to explain the perceived factors that influence Internet banking in Malaysia.…”
Section: Review Of Literaturementioning
confidence: 99%